Keabsahan Persyarikatan Muhammadiyah Sebagai Subyek Hukum Dalam Kepemilikan Hak Milik Atas Tanah - Anang Dony Irawan; Fadli Fadli (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this study is to find out shether the Muhammadiyah Confederation can be a valid legal subject on a certificate of property and to describe the procedure that must be taken by the center leaders of Muhammadiyah Confederation to obtain a certificate of property. This research was a normative legal research using legislation approach. The result of this research was Muhammadiyah confeceration as legal subject categorized as a legal entity belonging to land ownership which is used directly for the purpose of religious/worship and social welfare, and directly to support religious and social activities. The procedure that mus be taken by the Muhammadiyah Central Leaders to obtain the proprietary on land by requesting the acquisition of proprietary to the Head of the local national land agency by attaching the requirement according to the rules.